The Transatlantic Accordion and the Greek Key - Constantinidis, Charalambos (Études helléniques / Hellenic Studies, 2004)
America's handling of the post-September 11th crisis as well as the decision to go to war on Iraq created a rift of seemingly unprecedented proportions within the transatlantic alliance. The first five months of 2003 were marked by an exchange of bitter rhetoric, with Greece, as holder of the EU presidency, trying to mediate between America, Old Europe and New Europe. Nevertheless, the foundations of this transadantic partnership are much more solid than we often think. Politically and economically, America and Europe are interdependent to such a degree that a somerimes difficult partnership is much more affordable than an open rift. In this whole process, the role of Greece ought ro be clear-cut, yet respecting geopolitical realities both in the Medirerranean and beyond.